The paradoxical effect of long instructions on negative affect and performance: When, for whom and why do they backfire?. (June 2018) - Goemaere, Sophie; Beyers, Wim; De Muynck, Gert-Jan; Vansteenkiste, Maarten
Abstract: For reasons of bureaucracy and safety, astronauts on the International Space Station are provided with excruciatingly detailed instructions and a lack of decision-making power, even for simple routine tasks. Besides being time-consuming, many astronauts report feelings of demotivation, irritation, and even defiance when confronted with this working method. Anecdotic evidence suggests that this method leads to situations where astronauts read instructions diagonally or avoid checking in with mission support, thereby ironically increasing the risk of error making. There is a need to consider under which circumstances, for whom, and why the provision of long instructions could be detrimental for well-being and performance. An experimental study with LEGO assembly tasks examined whether length of instructions (i.e. short versus long) and task complexity (simple vs. complex) impact negative affect, motivational experiences and performance of participants ( N = 113, M age = 18.75 ± 2.46 years). Long instructions for simple tasks provoked greater feelings of irritation, diminished the perceived value of instructions, and negatively influenced productivity and accuracy. The negative effect of long instructions on irritation was explained via decreased perceived value. Additionally, the effect of length of instructions on irritation differed for participants high versus those low in need for achievement. Highlights: Astronauts are provided with very detailed instructions for simple routine tasks. Astronauts sometimes report feelings of demotivation, irritation, and defiance. This experiment studied the effects of length of instructions and task complexity. The negative effects of long instructions for simple tasks are discussed. The effect of instructions differed for participants high in need for achievement.